2021
DOI: 10.1080/14397595.2021.1886654
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical association with calcinosis cutis in early systemic sclerosis

Abstract: Objectives Calcinosis cutis is often found with systemic sclerosis (SSc). However the calcinosis cutis and its clinical association among SSc patients is limited. Our aims were to assess the prevalence of calcinosis cutis and its association with clinical features of SSc patients at early onset of the disease. Methods A cross-sectional study on clinical characteristics and hand radiographs of 120 newly diagnosed SSc patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
5
2
Order By: Relevance
“…Previous studies have also reported a higher likelihood of calcinosis development in SSc patients with longer disease duration, typically around 7–10 years [ 34 ]. In contrast, despite Muktabhant et al suggesting a potential higher risk of early calcinosis development in elderly patients [ 35 ], our cohort did not show age-related differences. The association between DU and calcinosis aligns with prior research indicating a higher likelihood of calcinosis in patients with severe vascular digital involvement [ 3 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have also reported a higher likelihood of calcinosis development in SSc patients with longer disease duration, typically around 7–10 years [ 34 ]. In contrast, despite Muktabhant et al suggesting a potential higher risk of early calcinosis development in elderly patients [ 35 ], our cohort did not show age-related differences. The association between DU and calcinosis aligns with prior research indicating a higher likelihood of calcinosis in patients with severe vascular digital involvement [ 3 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Prevalence of hand calcinosis in our series (6.9%) is lower than that reported in previous studies (10%–37.8%) [ 3 7 , 9 , 12 , 13 , 16 , 17 , 23 , 24 , 33 ]. But it is nearly in agreement with the recent study of Sakata and coworkers (10%) from Japan in 2019.…”
Section: Discussioncontrasting
confidence: 84%
“…They also confirmed a strong association between calcinosis and digital ischemia. A recent study by Muktabhant et al [ 37 ] aimed to identify common clinical features between SSc patients with and without calcinosis cutis and reported that patients with calcinosis cutis were significantly older than those without calcinosis cutis (every one-year increase of age provided the OR of calcinosis cutis detection of 1.05; 95% CI, 1.01–1.09). Interestingly, no association was found with the SSc subset or serology.…”
Section: Calcinosis Cutis and Systemic Sclerosismentioning
confidence: 99%